Philosophy 167: Class 6 - Part 9 - A New Approach- Emphasizing Mathematical Tractability. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Discusses the Archimedes sparrow; spirals; and mathematical tractability.; Opening line: "I wanna start now with this very opening paragraph and a half on the section on naturally accelerated motion."; Duration: 8:53 minutes.; Segment: Class 6, Part 9.